Increased Anxiety-Like Behavior in the Acute Phase of a Preclinical Model of Periodontal Disease - Varotto, Bruna Luiza Roim; Martinez, Raquel Chacon Ruiz; Gouveia, Flavia Venetucci; Antunes, Geiza Fernanda; Fabri, Gisele Maria de Campos; Ballester, Gerson; Antequera, Reynaldo; de Siqueira, Silvia Regina Dowgan Tesseroli; Fonoff, Erich Talamoni; Teixeira, Manoel Jacobsen; de Siqueira, José Tadeu Tesseroli (Frontiers in Neurology, 2020)
Periodontal disease (PD) is an infectious-inflammatory oral disease that is highly prevalent among adolescence and adulthood and can lead to chronic orofacial pain and be associated with anxiety, stress and depression. This study aimed to identify anxiety-like behaviours in the ligature-induced murine preclinical model of PD in different phases of the disease (i.e. acute versus chronic). Also, we investigated orofacial mechanical allodynia thresholds and superficial cortical plasticity along the orofacial motor cortex in both disease phases. To this aim, twenty-five male Wistar rats were randomly allocated in acute (14 days) or chronic (28 days) ligature-induced-PD groups and further divided into active-PD or sham-PD. Anxiety-like behaviour was evaluated using the elevated plus maze, mechanical allodynia assessed using the von Frey filaments test and superficial motor cortex mapping was performed with electrical transdural stimulation. We observed increased anxiety-like behaviour in active-PD animals in the acute phase, characterized by decreased number of entries into the open arm extremities (t(1,7)=2.42, p=0.04), and reduced time spent in the open arms (t(1,7)=3.56, p=0.01) and in the open arm extremities (t(1,7)=2.75, p=0.03). There was also a reduction in the mechanical allodynia threshold in all active-PD animals (Acute: t(1,7)=8.81, p<0.001; Chronic: t(1,6)=60.0, p<0.001), that was positively correlated with anxiety-like behaviours in the acute group. No differences were observed in motor cortex mapping. Thus, our findings show the presence of anxiety-like behaviours in the acute phase of PD making this a suitable model to study the impact of anxiety in treatment response and treatment efficacy.